MEKANISME PENGGUNAAN HAK INTERPELASI OLEH DEWAN PERWAKILAN RAKYAT DAERAH SUMATERA UTARA - Atika Sunarto (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
DPRD is the people's representative which is formed as a forum for the people in the region to share their aspirations. DPRD as a legislative institution in carrying out its functions has rights as regulated and stipulated in Article 159 to Article 160 of the Law Number 23 of 2014 concerning Regional Government, including the interpellation rights as the subject matter of this journal. Based on the background described above, this research will discuss how is the mechanism of the use of the interpellation rights by the Regional People's Representative Assembly of North Sumatra, and how are the interpellation rights and the legal obligations regarding the Regional Government. The reason of the DPRD of North Sumatera in using the authority of the interpellation right is because of the Regional Government's policy regarding BDB in the 2013 APBD. After the interpellation right was carried out, the results of the DPRD for North Sumatra Representatives received the Governor's answer and assumption that the importance of the Lower Assistance fund was to assist the regions in North Sumatra in carrying out the development. The mechanism of the use of the interpellation rights by the DPRD of North Sumatra is proposed by at least 15 (fifteen) DPRD members or more than 1 (one) faction. The proposal is accompanied by a document containing the policy material and the reasons for the inquiry request. The proposal from the DPRD leadership is submitted to the DPRD plenary meeting. The decision to approve or reject an application submitted to the Governor is determined in a plenary meeting of the DPRD. The legal consequences or consequences of the DPRD's interpellation rights largely depend on the facts and the evidence revealed in the investigation process and also on the DPRD members' analysis of the facts and evidence that have been revealed. If the DPRD members judge that the local government's actions are appropriate and correct, the questionnaire committee will provide support for the government's policy. Keywords: Interpellation Rights, Regional People's Representative Assembly of North Sumatra